Genetically Modified Organisms and the U.S. Retail Food Labeling Controversy: Consumer Perceptions, Regulation, and Public Policy. (September 2015) - Hemphill, Thomas A.; Banerjee, Syagnik
Abstract In this article, we address the public issue of mandatory Genetically Modified Organism (GMO) retail food labeling in the U.S., first by reviewing the policy arguments both in support and against labeling food containing GMOs; second, by describing the existing U.S. federal regulatory system pertaining to GMO labeling, and why it does not presently require labeling of food containing GMOs; third, by reviewing and interpreting the results of studies of American consumer attitudes toward mandatory GMO retail food labeling; fourth, by evaluating, through the utilization of issue life cycle analysis in the nonmarket environment, where the issue of GMO retail food labeling stands in the national public policy process; fifth, summarizing the state of scientific evidence addressing the safety of GMO foods and the existing regulatory and public policy environment for this issue; and sixth, offering legislative and litigation strategies for the mainstream food nonmarket strategy framework to formally assess the GMO industry to protect their interests and those of American consumers not concerned with GMO food ingredients, while offering a voluntary labeling strategy for firms responding to and recognizing the "rights" of American consumers who "choose" to purchase non‐GMO food products.